Care in the past : archaeological and interdisciplinary perspectives (Oxbow Books, 2016)
"Care-giving is an activity that has been practiced by all human societies. From the earliest societies through to the present, all humans have faced choices regarding how people in positions of dependency are to be treated. As such, care-giving, and the form it takes, is a central experience of being a human and one that is culturally mediated. Archaeology has tended to marginalise the study of care, and debates surrounding our ability to recognise it within the archaeological record have often remained implicit rather than a focus of discussion. These 12 papers examine the topic of care in past societies and specifically how we might recognise the provision of care in archaeological contexts and to open up an inter-disciplinary conversation, including historical, bioarchaeological, faunal and philosophical perspectives. The topic of 'care' is examined through three different strands: the provision of care throughout the life course, namely that provided to the youngest and oldest members of a society; care-giving and attitudes towards impairment and disability in prehistoric and historic contexts, and the role of animals as both recipients of care and as tools for its provision"--Publisher description.